Psychological Impact of the COVID-19 Pandemic on Dentists in Latin America’s Epicenter: São Paulo, Brazil - Rodrigues de Araujo, Carlos Ariel; Viana Ribeiro, Danielle; Boina de Oliveira, Danielle; Silva de Castilho, Gabriela; Jiménez, Manuel; Kerber Tedesco, Tamara; Camillo Jordão, Maisa; Fernandes Novaes, Tatiane; da Costa Palacio, Danielle; Heller, Debora (International Journal of Environmental Research and Public Health, 2023)
The present study aimed to assess the prevalence and associated factors of stress and anxiety symptoms among dentists during the COVID-19 pandemic in the state of São Paulo, Brazil. A structured questionnaire was sent electronically to 93,280 dentists with active registration in the Dental Council of São Paulo, Brazil, enquiring about information regarding the first-wave peak period in Brazil. Descriptive analyses of background characteristics, perceptions of preparedness, and psychological impact were calculated. Multiple logistic regression analysis was performed, and independent variables that showed p < 0.20 were used in the adjusted logistic regression model to compare the psychological impact on dental professionals. Among the 2113 respondents, female participants had 63% lower chance of reporting anxiety than males. Older dentists had a lower likelihood of reporting anxiety compared to 21–30-year-old dentists (p ≤ 0.05). Dentists working in the public health service were 1.78 times more likely to report anxiety than those who worked in private practice. Finally, dentists in the COVID-19 high-risk group and those with a family or team member with a positive COVID-19 diagnosis were more likely to have anxiety. This study can help dental and other healthcare professionals to better understand the consequences of COVID-19 in terms of mental health.
Keywords: anxiety; coronavirus; COVID-19; dentistry; mental health; SARS-CoV-2; stress; Scopus; JCR